Relationship between Leadership and Management Training and Enhancement of Principal’s Skills at Public Sector Secondary School Level (Journal of Social Sciences Review, 2023)
This research paper aimed to investigate the relationship between leadership and management training and the enhancement of skills of principals at the secondary level in Khyber Pakhtunkhwa. The study was motivated by the recognition of the crucial role that principals play in the success of secondary schools and the importance of their leadership and management skills. The research involved a comprehensive review of the role of principals at the secondary school level, the importance of training and professional development, and the specific challenges faced by principals in Khyber Pakhtunkhwa. In addition, the study involved the collection of data through a questionnaire from the trained secondary school principals in Khyber Pakhtunkhwa to gain insights into their experiences with leadership and management training and how it has enhanced their skills and abilities. Their input and impression provided support to find the gaps and improve further the training, its process and procedure. The results of the study provided valuable insights into the effectiveness of leadership and management training programs in enhancing the skills of principals at the secondary level in Khyber Pakhtunkhwa. The findings could also inform the development of policies and programs aimed at improving the quality of education in the region.
Keywords: DPD; Leadership; Management; Secondary School; Skills